FEATURES OF THE RAYNAUD’S SYNDROME COURSE IN PATIENTS WITH RHEUMATOID ARTHRITIS - Shtefiuk, O.V.; Yatsyshyn, R.I.; Herych, P.R.; Karpyuk, Yu.Ya.; Boychuk, V.B. (World of Medicine and Biology, 2020)
Often, patients with rheumatoid arthritis develop secondary Raynaud's syndrome, which is a prognostically unfavorable symptom of its course. Raynaud's syndrome is more common in patients with an existing rheumatoid factor in the blood serum. In patients with rheumatoid arthritis there is an impaired endothelium dependent vasoregulation in the shoulder artery, indicating the endothelial function disorder. In patients with rheumatoid arthritis with secondary Raynaud's syndrome, there are more pronounced signs of endothelial dysfunction, indicating a high risk of atherosclerosis and cardiovascular complications. The index of open capillaries permits to objectively assess the Raynaud's syndrome severity in patients with rheumatoid arthritis.
Keywords: rheumatoid arthritis; Raynaud's syndrome; endothelial dysfunction